Phytochemical Analysis and Biological Evaluation of Carob Leaf (Ceratonia siliqua L.) Crude Extracts Using NMR and Mass Spectroscopic Techniques - Venianakis, Themistoklis; Parisis, Nikolaos A; Christou, Atalanti; Goulas, Vlasios; Nikoloudakis, Nikolaos; Botsaris, George; Goričan, Tjaša; Grdadolnik, Simona Golič; Tzakos, Andreas G.; Gerothanassis, Ioannis P. (My University, 2024)
Carob leaves have gained attention for their bioactive properties and traditional medicinal uses, including as treatment for diabetes, digestive disorders, and microbial infections. The aim of this study was to explore the phytochemical composition of carob leaf acetone extracts using advanced spectroscopic techniques. The combined use of heteronuclear nuclear magnetic resonance (NMR) experiments with 1D selective nuclear Overhauser effect spectroscopy (NOESY) offers detailed structural insights and enables the direct identification and quantification of key bioactive constituents in carob leaf extract. In particular, the NMR and mass spectrometry techniques revealed the presence of myricitrin as a predominant flavonoid, as well as a variety of glycosylated derivatives of myricetin and quercetin, in acetone extract. Furthermore, siliquapyranone and related gallotannins are essential constituents of the extract. The potent inhibitory effects of the carob leaf extract on Staphylococcus aureus (MIC = 50 μg mL-1) and a-glucosidase enzyme (IC50 = 67.5 ± 2.4 μg mL-1) were also evaluated. Finally, the antibacterial potency of carob leaf constituents were calculated in silico; digalloyl-parasorboside and gallic acid 4-O-glucoside exert a stronger bactericidal activity than the well-known myricitrin and related flavonoids. In summary, our findings provide valuable insights into the bioactive composition and health-promoting properties of carob leaves and highlight their potential for pharmaceutical and nutraceutical applications.
Keywords: antimicrobial activity; carbohydrate digestive enzyme inhibition; carob leaf; flavonoids; galloyl derivatives; myricetin; mass spectrometry; NMR spectroscopy